Effect of ascorbate on plasminogen activator inhibitor-1 expression and release from platelets and endothelial cells in an in-vitro model of sepsis. Issue 4 (June 2015) - Swarbreck, Scott B.; Secor, Dan; Ellis, Christopher G.; Sharpe, Michael D.; Wilson, John X.; Tyml, Karel
<x xml:space="preserve">Abstract</x> The microcirculation during sepsis fails due to capillary plugging involving microthrombosis. We demonstrated that intravenous injection of ascorbate reduces this plugging, but the mechanism of this beneficial effect remains unclear. We hypothesize that ascorbate inhibits the release of the antifibrinolytic plasminogen activator inhibitor-1 (PAI-1) from endothelial cells and platelets during sepsis. Microvascular endothelial cells and platelets were isolated from mice. Cells were cultured and stimulated with lipopolysaccharide (LPS), tumor necrosis factor alpha (TNFα), or thrombin (agents of sepsis), with/without ascorbate for 1–24 h. PAI-1 mRNA was determined by quantitative PCR. PAI-1 protein release into the culture medium was measured by ELISA. In platelets, PAI-1 release was measured after LPS, TNFα, or thrombin stimulation, with/without ascorbate. In endothelial cells, LPS and TNFα increased PAI-1 mRNA after 6–24 h, but no increase in PAI-1 release was observed; ascorbate did not affect these responses. In platelets, thrombin, but not LPS or TNFα, increased PAI-1 release; ascorbate inhibited this increase at low extracellular pH. In unstimulated endothelial cells and platelets, PAI-1 is released into the extracellular space. Thrombin increases this release from platelets; ascorbate inhibits it pH-dependently. The data suggest that ascorbate promotes fibrinolysis in the microvasculature under acidotic conditions in sepsis.